2024
DOI: 10.3390/ijms25042060
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Hypoxia-Inducible Factors in Cancer

Saba Musleh Ud Din,
Spencer G. Streit,
Bao Tran Huynh
et al.

Abstract: In the realm of cancer therapeutics, targeting the hypoxia-inducible factor (HIF) pathway has emerged as a promising strategy. This study delves into the intricate web of HIF-associated mechanisms, exploring avenues for future anticancer therapies. Framing the investigation within the broader context of cancer progression and hypoxia response, this article aims to decipher the pivotal role played by HIF in regulating genes influencing angiogenesis, cell proliferation, and glucose metabolism. Employing diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Thus, by escalating knowledge on HIF-1α control, increased literature about HIF-1α control and influence can lead to the development of improved treatment for ischemic diseases, inflammatory diseases, and cancer. While there are currently many barriers, it has been demonstrated that examining the possibility of focusing on HIF-1α and its therapeutic potential reveals the prospect of building more effective and individualized treatment protocols [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Thus, by escalating knowledge on HIF-1α control, increased literature about HIF-1α control and influence can lead to the development of improved treatment for ischemic diseases, inflammatory diseases, and cancer. While there are currently many barriers, it has been demonstrated that examining the possibility of focusing on HIF-1α and its therapeutic potential reveals the prospect of building more effective and individualized treatment protocols [ 39 ].…”
Section: Reviewmentioning
confidence: 99%